Environment friendly crosslinked chitosan as a matrix for selective adsorption and purification of lipase of aspergillus niger - Trimukhe, K. D.; Mahadik, N. D.; Gokhale, D. V.; Varma, Anjanikumar (International Journal of Biological Macromolecules, 2008)
Chitosan and its derivatives have been used as affinity matrices for purification of lipase from Aspergillus niger NCIM 1207. Trimellitic anhydride (TMA)-crosslinked deacetylated chitin adsorbed lipase selectively, yielding approximately 5-fold purification of the crude lipase with 70% yield. Further 9-fold purification occurred on eluting through Sephacryl-100. These results suggest that chitosan derivatives can be used as inexpensive biopolymer matrices for the purification of lipases for industrial applications. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Chitosan; Lipase; Matrix; Purification

Effect of mixed acid catalysis on pretreatment and enzymatic digestibility of sugar cane bagasse - Pal, Siddhartha; Joy, Shereena; Kumbhar, Pramod; Trimukhe, K. D.; Varma, Anjanikumar; Padmanabhan, Sasisanker (Energy & Fuels, 2016)
Aqueous pretreatment using homogeneous acid catalyst is considered as a low-cost technology in the production of lignocellulosic bioethanol. To establish the synergism of mixed acids, pilot-level aqueous pretreatments of bagasse covering a wide range of combined severity (CS) were carried out. To investigate the effect of application of mixture of acids on xylose hydrolysis as well as glucose hydrolysis via pretreatment and enzymatic hydrolysis, the following three combinations of acids were explored: (1) oxalic acid + sulfuric acid (organic + mineral acid), (2) phosphoric + sulfuric acid (mineral acids), and (3) ferric chloride + sulfuric acid (Lewis acid with a mineral acid). Of the pretreatments evaluated, the synergism was most pronounced for the combination of sulfuric and phosphoric acid, which resulted in more than 90% conversion of hemicellulose to xylose and 70% conversion of cellulose to glucose through enzymatic hydrolysis. Fourier transform infrared (FTIR) studies of pretreated samples showed higher syringyl/guaiacyl (S/G) ratio for sulfuric and phosphoric acid combination pretreatment, leading to higher enzymatic conversion. FTIR and dynamic light scattering (DLS) experiments conducted on pretreated sugar cane bagasse provided useful correlation with regard to the pretreatment type, particle size, and enzymatic hydrolysis.